KORELASI NILAI INHERENT MOISTURE TERHADAP NILAI CALORIFIC VALUE STANDAR AMERICAN SOCIETY OF TESTING AND MATERIALS (ASTM) DI PT TRIYASA PIRSA UTAMA SAMARINDA - Josephine, Josephine; Pasaribu, Subur P.; Panggabean, Aman Sentosa (PROSIDING SEMINAR KIMIA, 2024)
Coal is one of the main fuel sources for electricity generation in Indonesia. Coal contains inherent moisture water content and chemical calorific value. The Inherent Moisture value in coal is one of the main characteristics of coal that determines the quality of the coal. The calorific value of coal was determined from the values ​​of Total Moisture, Ash Content and Total Sulfur which are the determining parameters for coal quality. The aim of this research is to determine the correlation between the Inherent Moisture value and the Calorific Value of coal with ASTM standards. This research was conducted at PT Triyasa Pirsa Utama Samarinda using 10 different coal samples to analyze the Inherent Moisture value and Calorific Value. Based on the data from the analysis and graphs, a correlation between the Inherent Moisture (IM) and Calorific Value (CV) values ​​is inversely proportional, where the higher the IM value, the lower the CV value in the coal sample. The factors that influence changes in IM and CV values ​​are climate, weather, coal storage time and coal grain size degradation. Keywords: Coal, Moisture, Calorific Value, ASTM Standard.